Immunomodulatory Activity of Yogurt Fortified with Honey and Rosella (Hibiscus sabdariffa L.) on Reactive Oxygen Intermediate (ROI) and Nitric Oxide (NO) Secretion - Nurkhasanah Mahfudh; Rina Novitasari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Raise the body's immune system. Rosella (Hibiscus sabdariffa Linn.) is known to have anthocyanin compounds that have antioxidant and immunomodulatory effects. The aim of this research is to know the effect of immunomodulator yogurt which fortified by rosella (Hibiscus sabdariffa L.) extract to increase the secretion of Reactive Oxygen Intermediate (ROI) and Nitric Oxide (NO). This research was conducted in vivo using 25 male mices with Balb/C strain divided into 5 groups: normal group, plain yogurt treated group and 2%, 4%, 8% rosella yogurt treated group. Treatment was given for 21 days orally. On the 22nd day the mice were sacrificed by taking peritoneum macrophage cells and then tested the secretion of Reactive Oxygen Intermediate (ROI) and Nitrite Oxide (NO). The results showed that there was an increase of ROI and NO secretion in 2%, 4%, and 8% rosella yoghurt treated groups compare to plain yoghurt. The fortification of yoghurt with rosella extract and honey increase the potency of yoghurt in increasing the immunomodulatory activity